Behavioral Risk Factors for Non-Communicable Disease Among Rural Adults In Andhra Pradesh - Bodhare, Trupti N; Venkatesh, Kanchi; Bele, Samir; Kashiram, Gali; Devi, Sujata; Vivekanand, Achanta (National Journal of Community Medicine, 2013)
Introduction: Non-communicable diseases (NCDs) are the leading cause of death in rural parts of Andhra Pradesh. Most of the risk factors for NCDs are modifiable and can be controlled to reduce incidence and to ensure better outcomes for those having NCDs. Objectives: To estimate the prevalence of various behavioral risk factors for NCDS in rural area and to evaluate the socio-demographic characteristics associated with these risk factors. Material and Methods: A cross sectional study was conducted in rural area of Karimnagar among 410 participants. Various risk factors assessed were smoking and alcohol intake, physical inactivity, obesity, hypertension and stress among participants. Results: The mean age of the participants was 56.41 ± 11.90 years. Male accounted for 55.6% of the total sample, 34.9% were illiterate and 70.7% belonged to an upper lower class. Presence of at least one risk factor was observed among 76.3% of participants. The prevalence of hypertension was 38.5% among participants, 24.6% were current smokers whereas 29.8% were current alcohol users. Stress was exhibited by 24.9% and 25.9% were physically inactive. A binary logistic regression analysis revealed that older age (p = 0.000), male gender (p = 0.001), illiteracy (p = 0.007) and lower socio-economic status (p = 0.001) were associated with the presence of at least one risk factor. Conclusion: High prevalence of risk factors among rural population warrants an immediate attention. There is a need for careful monitoring and control of non-communicable disease risk factors in rural area.